دراسة الناقلية الضوئية لفيلم رقيق من بلاستيك البولي ستايرين (PS) المحضر بطريقة التغطية بالدوران (Spin coating) - قنجراوي, ختام (Latakia University Journal -Engineering Sciences Series, 2017)
درست في هذا البحث العلاقة بين الناقلية الضوئية opϬ ( Optical Conductivity ) وكلاً من طاقة الفوتون (hν ) , ومعامل الامتصاص α (absorbance coefficient ), والنفوذية T ( Transmittance ), ومعامل الانكسار no( refractive index ), ومعامل العزل الكهربائي الحقيقي والتخيلي (εr , εi) (real and imaginary part of dielectric coefficient), وv سرعة دوران جهاز الترسيب (Spin Coater), وذلك عند طول موجة محدد هو (600nm), لفيلم رقيق نقي (pure thin film) محضر من مادة عضوية بوليميرية هي بولي ستايرين (Polystyrene), بطريقة التغطية بالدوران (Spin Coating), من أجل سرعات هي (1000, 2000, 3000) RPM في درجة حرارة الغرفة وتحت الضغط الجوي النظامي. تبين من هذه الدراسة أن فيلم PS الرقيق هو فيلم نفوذ للأشعة تحت الحمراء القريبة, حيث تراوحت نفوذيته بين (85-90)%, وأن الناقلية الضوئية opϬ تزداد بازدياد طاقة الفوتون, فتأخذ أعلى قيمة لها 1.67 X 1014 1/sec عند الطاقة , ( hν = 3.1 ev )الموافقة لطول الموجة ( λ= 400nm) من أجل السرعة 1000RPM أي أنها تنشط في مجال الأشعة المرئية. ووجدنا أنها تتناقص مع ازدياد سرعة دوران ترسيب البوليمير.وكانت قيم Eg للانتقالات الالكترونية المباشرة المسموحة مساوية الى (2.5ev) , (2.4ev) , (2.3ev) في الأفلام المحضرة وفق السرعات 1000RPM, 2000RPM, 3000RPM على الترتيب. أما للانتقالات الالكترونية المباشرة الممنوعة فكانت تساوي (2.3ev) , (2.2ev) , (2.1ev) للأفلام المحضرة على الترتيب. بينما كانت أكبر قيمة لطاقة يورباخ Eu تساوي الى (163mev) الموافقة للسرعة 1000RPM وأقل قيمة لها تساوي (109mev) الموافقة للسرعة 3000RPM.In this research we studied the relationship between the optical conductivity Ϭop and photon energy (hν), the absorbance coefficient (α), transmittance (T), the refractive index (no), and the real part and imaginary part of dielectric constant (εr, εi), the spinning velocity of deposition device (v), for a specific wave length (600nm), for a pure thin film prepared from an organic polymer material, Polystyrene (PS), by spin coating technique, on three velocities ( 1000-2000-3000)RPM, in room temperature and 1atm. It was shown that the PS film is a transmittive film with a transmittance values reach ( 85 – 90 )% in the infrared region, and the optical conductivity Ϭop increased with the photon energy, and for the velocity 1000RPM it took the highest value ( 1.67 X 1014 )1/sec, at the photon energy (hν =3.1 ev) and the wave length ( λ= 400nm ), which means that the optical conductivity Ϭop is active in the visible region, and also it decreases with the spinning velocity.The values of energy gap for allowed direct transitions were (2.5ev), (2.4ev), (2.3ev) for the films prepared on 1000RPM, 2000RPM, 3000RPM, and for the forbidden direct transitions were (2.3ev), (2.2ev), (2.1ev) respectively .The biggest value of Urbach energy Eu was (163mev) on the velocity 1000RPM and the lowest value was (109mev) on the velocity 3000RPM.